EVALUASI REPRODUKSI SAPI FRIESIAN HOLSTEIN PADA BERBAGAI PARITAS - Hadi, Sutrisno; Ari Kustanti, Nita Opi; Esti, Risma Novela (AVES: Jurnal Ilmu Peternakan, 2023)
The purpose.of this research is to evaluate the.reproduction of Holstein Friesian cows at various parities. The study was conducted at PT Greenfields Indonesia.Farm 2 located in Pijiombo.Hamlet, Ngadirenggo.Village, Wlingi District, Blitar. The research material used was 327 Holstein Friesian cows at parities two, three, and four, with an estimated 109 cows per parity. The variables used in the evaluation were services.per conception (S/C), conception.rate (CR), days.open (DO), and calving.interval (CI). The method used in this research was a field study using secondary data. The collected data underwent analysis through analysis of variance (ANOVA), and in case of a significant effect, Duncan's multiple range test (DMRT) was applied for further examination. The results showed.that the higher the parity of the milking cows, the lower the reproductive evaluation results (P<0.05). Parity II had the most ideal reproductive results with a.service per conception value of 1,64±0.84a times, conception rate of 55,96%, days open of 88,01±27,56a days, and calving interval of 365,71±28,38a days compared to parities III and IV which showed lower results with service per conception values of 1,95±1,17b times; 2,15±1,24b times, conception rates of 50,45%; 42,2%, days open of 99,55±39,20b days; 104,83±40,89b days, and calving intervals of 378,16±39,26b days; 383,88±40,81b days This research concludes that the higher.the parity, the lower.the reproductive evaluation results, including service per.conception (S/C), conception rate (CR), days.open (DO), and calving.interval (CI).